Purification and Characterization of Novel Cyclodextrin Glucanotransferase from Bacillus sp. SK13.002 - Sun, T.; Jiang, B.; Pan, B.L. (Asian Journal of Chemistry, 2011)
Bacillus sp. SK13.002 was found to be a novel alkaliphilic cyclodextrin glucanotransferase (CGTase) producing strain. Two CGTase isozymes (CGTase-1 and CGTase-2) could be obtained following precipitation with ammonium sulphate as well as DEAE-Sepharose and Superdex 75 gel chromatography. After purification, the specific activity was increased from 0.49 U/mg (for the crude enzyme) to 9.47 and 8.83 U/mg for CGTase-1 and CGTase-2, respectively. Results obtained from SDS-PAGE showed that the enzyme was purified to homogeneity, with the molecular weight of CGTase-1 and CGTase-2 being estimated to 67.5 and 46.8 kDa and confirmed by LC/MS to be 67.6 and 47.3 kDa, respectively. CGTase-1 exhibited optimum temperature and pH of 65 ºC and 8.0, whereas those of CGTase-2 were 60 ºC and 6.5, respectively. Both CGTase isozymes were found stable at relatively high temperatures and in a very wide range of pH values. Following incubation with 5 % (w/v) soluble starch at 65 ºC and pH 8.0 for 24 h, CGTase-1 produced 36.9 g/L cyclodextrins comprising 81 % ß- cyclodextrin. Present findings provided an efficient method for the industrial production of ß- cyclodextrin from starch.